(SLR) Systematic Literature Review: Conflict Management: Turning Challenges into Opportunities in Islamic Education - Zulfiqar Ahsani Darojat; Muhammad Azhar (Green Publisher Indonesia, 2026)
Conflict is an inevitable phenomenon in every organization, including Islamic Religious Education institutions. Conflict is often perceived as a threat, but if managed properly, it can become a source of innovation and organizational progress. This study aims to explore conflict management theories, strategies, and practices within IRE environments, focusing on transforming challenges into opportunities. It employs the Systematic Literature Review (SLR) method to examine the theory, strategies, and practices of conflict management in the Islamic Religious Education environment, with a focus on turning conflict challenges into opportunities. The results show that conflict management approaches based on dialogue, mediation, deliberation, and Islamic values such as shura, tabayyun, and ishlah deliberation are effective in creating peaceful resolutions and strengthening organizational culture. Visionary and inclusive leadership, along with an adaptive organizational culture, are key factors in transforming conflict into opportunities to strengthen the quality of education and institutional productivity. Practical implications include the importance of conflict management training for organizational leaders and members, as well as the formation of cross-functional conflict management teams. Thus, conflict management in Islamic Religious Education is not only about resolving conflicts but also about creating momentum for character development, innovation, and continuous progress.